ATTITUDE OF PUBLIC TOWARDS COVID-19 VACCINE: An Exploratory Study in Pakistan - Eman, Saima; Jha, Ravi P.; Patel, Priyanka; Singh, Mayank; Sanawar, Memoona; Kazmi, Umm E Rubab; Shukla, Meenakshi (Revista Ciências Humanas, 2022)
Background: COVID-19 is a deadly viral infection that kills many people throughout the globe. The goal of this study was to find out how people in Pakistan felt about the COVID-19 vaccine. Method: Convenience and respondent-driven sampling method was used to conduct an online survey with 15 closed- and open-ended questions to a sample of 330 participants. The proportion of people who had a good attitude towards vaccination vs. those who had a negative attitude towards vaccination was revealed by the closed-ended questions. The open-ended questions elicited qualitative data on why people accepted or rejected the vaccination. Results: 62.9% of the respondents intended to use the COVID-19 vaccine and around 80% were younger than 50 years. 71.3% married, and 69.3% of the working population were willing to accept vaccination. Males are 1.97 times more likely (OR: 1.97, CI: 1.08-3.58) to use COVID-19 vaccine than females. Higher age groups were more likely to accept vaccination. The working population (82%) was more likely (OR: 1.82, CI: 1.08-3.58) to use the COVID-19 vaccine than the non-working population. Conclusion: This study helps to identify the attitudes of people and has implications for COVID-19 immunization efforts in Pakistan for various population segments.